Cardioprotective Effects of n-3 Polyunsaturated Fatty Acids: Orchestration of mRNA Expression, Protein Phosphorylation, and Lipid Metabolism in Pressure Overload Hearts - Li, Xiang; Tan, Weijiang; Zheng, Shuang; Zhang, Junjie; Zhu, Caiyi; Cai, Chun; Chen, Honghua; Yang, Chenqi; Kang, Le; Pan, Zhanhong; Pyle, W. Glen; Backx, Peter H.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Pressure overload leads to hypertrophic remodeling of the heart, and can result in dilated cardiomyopathy. The beneficial effects of n-3 polyunsaturated fatty acids (n3-PUFAs) in heart disorder have been well recognized. However, the molecular mechanisms underlying their protective effects against cardiomyopathy are still overlooked. Methods Pressure overload in mice induced by eight weeks of transverse aortic constriction (TAC) was used to introduce dilated cardiomyopathy (DCM). A transgenic fat-1 mouse model carrying n-3 fatty acid desaturase gene fat-1 gene from Caenorhabditis elegans was used to study the beneficial mechanism of n3-PUFAs in this disease. Echocardiography, transmission electron microscopy, and histopathological analyses were used to evaluate the structural integrity and function in pressure overloaded fat-1 hearts, mRNA sequencing, label-free phosphoprotein quantification, lipidomics, and western blotting were used to examine the beneficial roles of n3-PUFAs in the heart. Results Compared with WT hearts, cardiac function was significantly improved (C57BL/6J vs Fat-1: 45% vs. 35%) and the internal diameters of the left ventricles at systole and diastole were both reduced the fat-1 pressure overload hearts. The mitochondrial morphology and dynamics were maintained by endogenous n-3 PUFAs in pressure overload. Furthermore, the quantitative phosphoproteomic analysis revealed that various phosphoproteins were activated in fat-1 transgenic hearts, the improved mitochondrial structure and function were associated with restoration of the expression levels of mitochondrial respiratory chain complexes and the profile shifts of oxylipins derived from n-3 and n-6 PUFAs. Conclusions Endogenous n-3 PUFAs prevented cardiac remodeling and protected cardiac function in DCM, and the protective effects were exerted through regulating phosphorylation signaling and mitochondrial oxidative phosphorylation.